The Leadership of the Principal at SD Negeri Bejen in Implementing the Independent Curriculum - Rita Nurhayati; Nina Oktarina (Vifada Journal of Education, 2026)
This study aims to examine the transformational leadership of the principal in implementing the Merdeka Curriculum at SD Negeri Bejen, Bejen District, Temanggung Regency, focusing on leadership strategies, roles, and efforts to overcome implementation challenges. This study employed a qualitative descriptive approach conducted from February to April 2026. The research site was selected purposively due to its implementation of the Merdeka Curriculum. Data were collected through in-depth interviews, observations, and documentation involving the principal, teachers, and educational staff. Informants were selected using purposive and snowball sampling techniques until data saturation was achieved. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, with data validity ensured through source, technique, and time triangulation. The findings reveal that the principal implemented transformational leadership through six key aspects: curriculum planning, implementation support, academic supervision, communication and motivation, resource management, and continuous evaluation. The principal encouraged teacher involvement, strengthened professional learning communities, facilitated training programs, and optimized school resources to support curriculum implementation. However, challenges remained, particularly limited infrastructure and the suboptimal implementation of deep learning. This study implies that transformational leadership plays a crucial role in sustaining curriculum reform by fostering teacher competence, collaboration, and continuous improvement. Future studies are recommended to explore transformational leadership practices in diverse educational contexts